Diversity of endophytic fungi from medicinal plants Dysosma difformis (Hemsl & E.H. Wilson) T.H. Wang collected in Ha Giang and Lai Chau - Hoa, Tran Thi; Thu Giang, Nguyen; Hong Ha, Nguyen Thi; Huyen, Tran Thi; Tien Phat, Do; Hoang Ha, Chu; Bich Ngoc, Pham; Ho Quang, Tran (Vietnam Journal of Biotechnology, 2023)
Plant endophytes are an interesting group of microorganisms that colonize the internal tissues of living plants and do not cause any disease symptoms in the host plant. It exists in different parts of plants, such as roots, leaves, and stems, and significantly affects the formation of metabolic products in plants by promoting the accumulation of important secondary metabolites. The present study focused on analyzing the diversity and distribution of endophytic fungi related to different tissues from samples of the medicinal plant Dysosma difformis (Hemsl & E.H. Wilson) T.H. Wang collected in Ha Giang and Lai Chau, in which the isolates from roots were 27 strains (50.94%), 12 strains from stems (22.64%), and 14 strains from leaves (26.42%). Based on the isolates, we analyzed the fungal diversity through seven different diversity indices. The results showed that isolates’ diversity was similar to the endophytic fungal population in tissues of D. difformis distributed in different vegetation in Vietnam. Specifically, Shannon's index showed the highest diversity in roots (H′ = 2.673), followed by stems (H′ = 2.162) and leaves (H′ = 2,054). Similarly, species richness was highest in roots (Dmg = 4,551; Dmn = 3,079) and stem (Dmg = 4,024; Dmn = 3,175) and lowest in leaves (Dmg = 3.41; Dmn = 2,405). However, the Simpson diversity index showed that the endophytic fungal community was most abundance in leaves (1-D = 0.911), followed by stems (1-D = 0.897) and roots (1-D = 0.867). In addition, the Sorensen index of 0.615 shows the average similarity in species composition between the two sites, Ha Giang and Lai Chau. This is the first report on the diversity of endophytic fungi isolated from D. difformis, paving a potential way for screening endogenous fungal strains capable of producing important secondary compounds.